« S. » ou « M. » ? Voyage et auctorialité dans Histoire d’un voyage de six semaines (1817), de Mary Shelley et Percy Bysshe Shelley - Anne Rouhette (Viatica)
History of a Six Weeks’ Tour is travel narrative written by Percy Bysshe Shelley and Mary Shelley in 1817 and raises two questions surrounding the literary authority and the collaborative creation of the work. Indeed, the diary is based on a shared system of writing in which there is a clear alternation of juxtaposed voices. Based on a complex process of textual composition, History of a Six Weeks’ Tour reveals a shared life writing process, but also the existence of similar thoughts as they are nurtured through discussions with the other.